2016
DOI: 10.1038/nrrheum.2016.93
|View full text |Cite
|
Sign up to set email alerts
|

The brain–joint axis in osteoarthritis: nerves, circadian clocks and beyond

Abstract: Osteoarthritis (OA) is a prevalent and debilitating joint disease for which ageing, obesity and chronic inflammation are known risk factors. The central, peripheral and autonomic nervous systems are essential in all metabolic systems, and emerging evidence suggests a role for these systems in OA. In the past few years, metabolic diseases, such as obesity or diabetes, have been linked to disruption of circadian rhythms that are tightly regulated by the nervous system, whereas inflammatory and autoimmune disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 116 publications
(128 reference statements)
2
55
0
Order By: Relevance
“…Although elevated proinflammatory cytokine levels account for about half of cancer patients with altered circadian function, other mechanisms are most likely involved, including drug-induced CTS disruption, blunted synchronizers from disrupted feeding routine, minimal and untimely light exposure, or circadian alterations mediated by other brain areas. Hence, systems medicine approaches encompassing all factors toward CTS strengthening would not limit their usefulness to cancer, but could be applied to other chronic conditions, such as joint (Berenbaum and Meng, 2016), renal (Koch et al, 2009), liver (Tahara and Shibata, 2016), cardiovascular (Portaluppi et al, 2012; Smolensky et al, 2015c), metabolic (Asher and Schibler, 2011; Bass, 2012), neurologic (Smolensky et al, 2015b; Videnovic and Zee, 2015), and psychiatric (Wulff et al, 2010; McClung, 2013) diseases. Indeed, altered circadian function has been described in several diseases of the aforementioned systems, and their function has been shown to be affected by circadian disruption in otherwise healthy subjects (Reddy and O'Neill, 2010; Roenneberg and Merrow, 2016).…”
Section: Cts Disruptionmentioning
confidence: 99%
“…Although elevated proinflammatory cytokine levels account for about half of cancer patients with altered circadian function, other mechanisms are most likely involved, including drug-induced CTS disruption, blunted synchronizers from disrupted feeding routine, minimal and untimely light exposure, or circadian alterations mediated by other brain areas. Hence, systems medicine approaches encompassing all factors toward CTS strengthening would not limit their usefulness to cancer, but could be applied to other chronic conditions, such as joint (Berenbaum and Meng, 2016), renal (Koch et al, 2009), liver (Tahara and Shibata, 2016), cardiovascular (Portaluppi et al, 2012; Smolensky et al, 2015c), metabolic (Asher and Schibler, 2011; Bass, 2012), neurologic (Smolensky et al, 2015b; Videnovic and Zee, 2015), and psychiatric (Wulff et al, 2010; McClung, 2013) diseases. Indeed, altered circadian function has been described in several diseases of the aforementioned systems, and their function has been shown to be affected by circadian disruption in otherwise healthy subjects (Reddy and O'Neill, 2010; Roenneberg and Merrow, 2016).…”
Section: Cts Disruptionmentioning
confidence: 99%
“…Disruption of circadian clocks has long been associated with a range of metabolic disorders including obesity , metabolic syndrome , and type II diabetes . Recently, microbiome dysbiosis has emerged as the mechanistic link connecting metabolic diseases and circadian clock disruption (Fig ).…”
Section: Impact Of Host–microbiome Circadian Crosstalk On Health and mentioning
confidence: 99%
“…Though the role of BMAL1 clock gene is central to regulating the circadian oscillations and RA joints show abnormal cytoplasmic localization of BMAL in response to TNF-α induction, the extent of BMAL1 disruption in RA state along with other core clocks remains to be determined. catabolic effects and destroy matrix but also suppress the anabolic pathways by inhibiting Sox9 and Col2a1 expression, further impairing tissue repair (Figure 3) (Guo et al, 2015;Berenbaum and Meng, 2016). Guo et al (2015) demonstrated that exposure to catabolic cytokines IL-1β, but not TNF-α, severely disrupted circadian gene expression rhythm in cartilage.…”
Section: Figurementioning
confidence: 99%
“…Melatonin, a circadian-controlled product secreted by the pineal gland, has been suggested as a potential link between circadian rhythms and joint diseases, including RA and OA (Yoshida et al, 2014a,b;Berenbaum and Meng, 2016). Melatonin and its derivatives are wide-ranging free radical detoxifiers and antioxidants, because of their potential scavenging of free radicals of oxygen species (ROS) and nitrogen species (RNS) and to boost the expression and activity of glutathione and antioxidant enzymes (Reiter et al, 2016).…”
Section: Introductionmentioning
confidence: 99%